The research of process of CdTe passivation coverings formation on epitaxial layers CdхHg1-хTe for creation of IRphotodetectors. - V. V. Arbenina; T. V. Danilova; A. S. Kashuba; E. V. Permikina (Тонкие химические технологии)
The features of formation passivation coverings of cadmium telluride on epitaxial layers CdхНg1-хТе used for manufacturing of matrix photodetectors of the IR-range are investigated. The laws of process of passivation coverings creation by a method of «the hot wall » are established at unitary and repeated use of CdTe source.